Parasitoid community structure of leaf miner Liriomyza spp. (Diptera: Agromyzidae) and the rate of parasitization on vegetable crops in Lesser Sunda Islands, Indonesia - SRI WAHYUNI; I WAYAN SUPARTHA; ROSICHON UBAIDILLAH; I NYOMAN WIJAYA (Society for Indonesian Biodiversity, 2017)
Wahyuni S, Supartha IW, Ubaidillah R, Wijaya IN. 2017. Parasitoid community structure of leafminer Liriomyza spp. (Diptera: Agromyzidae) and the rate of parasitization on vegetable crops in Lesser Sunda Islands, Indonesia. Biodiversitas 18: 593-600. Parasitoids such as leafminer have long been known to play an important role in reducing potential pest populations. However, detailed information about the parasitoid community in many agroecosystems is still very limited. To attempt to address this data gap, we assessed the rate of parasitism, diversity, abundance and dominance of leafminer parasitoids in different agroecosystems. The survey was carried out from February to July 2015 in Lesser Sunda islands of Lombok, Sumbawa, Flores and Timor. Samples were taken from three different vegetable ecosystem types the forest edge (H1), agricultural (H2) and settlement (H3). In each ecosystem, 50 leaves were sampled from 20 kinds of vegetable crops attacked by Liriomyza spp. Samples were taken five times per location every week. The sampling results found three distinct species of leafminer flies present: Liriomyza huidobrensis, L. sativae, and Chromatomyia horticola. The sampling also successfully identified 7 other parasitoids with parasitization rates between 0.09%-32.58% i.e. Neochrysocharis formosa (8.20%-32.58%), Hemiptarsenus varicornis (4.57%-24.21%), Opius chromatomyiae (0.88%-22.35%), Opius dissitus (0.49%- 5.08%), Neochrysocharis okazakii (0.69 %-1.24%), Asecodes deluchii (0.51%-5.89%) and Gronotoma micromorpha (0.09%-0.34%). Indices of abundance (R) and diversity (H') were also calculated, with the highest species abundance being found on the Lombok and the lowest on the Sumbawa. Neochrysocharis formosa abundance was found in all the islands sampled, while the dominance (D = 0.43) was found on the Sumbawa. N. formosa was found to have the highest population abundance and parasitism rate, and was found on every island in Lesser Sunda including on the Lombok (1853 adult; 31.16%), Sumbawa (472 adult; 8.2%), Flores (1117 adult; 15.96 %) and Timor (984 adult; 22.18%). The results of these studies suggest a strong need for effective pest control policies for Liriomyza spp. in the research locations, as well as for other vegetable crops in Indonesia